Técnica adaptada para determinação do índice proliferativo AgNOR em amostras citológicas de mastocitoma canino - Mann, Thaís Rapachi (2021)
Mast cell tumors are neoplastic proliferations of mast cells, uncommon in most species and frequent in pets. Majority of MCT occur in the dermis and subcutaneous tissue and the etiopathogenesis is unknown. Its clinical appearance varies a lot and must always be considered potentially malignant, and may be associated with the expression of clinical signs caused by the release of vasoactive amines that are present in mast cell granules. Metastases should be searched and, whenever possible, surgical removal for histological grading of the tumor, which is the gold standard exam in the prognostication of mast cell tumor. The cytopathological exam is the initial, inexpensive, fast, and non-invasive tool for diagnosing mast cell tumors. Recently, cytological grading systems for mast cell tumors have been proposed, enabling the early identification of the tumor grade, which can be useful to plan treatment strategies and discuss the prognosis with the dog's owner. Other markers should be used to identify the proliferative index of the tumor, such as the count of argyrophilic nucleolar organizer regions (AgNORs). This work aims to generate information to advise about the presentation of patients with mast cell tumors in association with the AgNOR proliferative index. Thus, two manuscripts were produced about the practical approach of the canine patient with mast cell tumor. In the first manuscript, a technique to determine the AgNOR proliferative index collected from cytology was standardized, through which it was possible to impregnate slides previously stained with routine dyes, thus anticipating the tumor proliferative index. In the second manuscript, 63 cases of dogs with mast cell tumors were selected, which had the AgNOR index related to sex, breed, location and cytological grade. The findings demonstrate that there is no sexual or racial predisposition to high AgNOR indices, but in some anatomical sites the development of mast cell tumors has higher proliferative indices. It was also observed that high AgNOR indices are associated with high cytological grade mast cell tumors, which may represent a worse prognosis. Thus, it is suggested to evaluate the patient with mast cell tumor in the pre-surgical period by clinical staging, cytological analysis and cytological AgNOR index for the proper targeting of therapeutic strategies. The use of the AgNOR proliferative marker is useful because it is quick and easy to perform and provides support for the clinical approach having better results, helping to define the need for complementary therapeutic procedures in addition to surgical removal.